Industrial-strength denial : eight stories of corporations defending the indefensible, from the slave trade to climate change - Freese, Barbara (Barbara E.) (University of California Press, 2020)
"This book tells the stories of eight major campaigns of corporate denial-the lies, delusions, and rationalizations that emerge when people working in competitive, profit-driven group enterprises are faced with powerful evidence that they are causing harm. Tobacco is the poster-child of this phenomenon, but denial comes from people selling many other risky products, creating workplace hazards, or releasing dangerous pollutants. In almost every case, the story begins with an exciting discovery-of, for example, a New World, a new element or chemical, a new means of mass production, or a new way of packaging financial risk. An industry races to exploit that discovery and succeeds, sometimes changing society along the way. And in each case this commercial activity causes a grave harm, to other people or the planet. Those outside the industry find evidence of this harm, raise the alarm, and a public debate ensues. Corporate representatives offer a flurry of denials, perpetuating the harm by blocking policies that would reduce it. The specific denials-which are the focus of this book-vary, but the themes echo from campaign to campaign. The stories in this book stand as a reminder of why corporate activity needs to be monitored, challenged, and regulated"--